Features of the legal status of the civil service manager in local prosecutor - Naulik, Nataliia; Horzov, Anatolii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article analyzes the current legislation and enshrines the legal status of the head of the civil service at the local prosecutor’s office in it. The basic terminological discrepancies in the legislation are defined and possible options for resolving a legal conflict in the settlement of this issue are proposed.